Steel plate

By optimizing the chemical composition and metal structure of the steel plate, uniformly dispersing martensite and controlling its distribution, the problem of difficulty in taking into account strength, formability and appearance during the forming process of high-strength steel plates is solved, and the high strength, good formability and excellent appearance of the steel plates are achieved.

CN119855929APending Publication Date: 2025-04-18NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380063820.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-09-08
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

It is difficult to take into account the strength, formability and appearance during the forming process of existing high-strength steel plates, especially the appearance after forming.

Method used

By optimizing the chemical composition and metal structure of the steel plate, specific measures include uniform dispersing martensite in the metal structure and controlling the average particle spacing and distribution uniformity of martensite through specific annealing treatment.

Benefits of technology

While increasing the strength of the steel plate, it maintains good forming properties and excellent after-forming appearance, significantly suppressing the occurrence of poor appearance such as ghost lines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005297603790000281
    Figure BDA0005297603790000281
  • Figure BDA0005297603790000291
    Figure BDA0005297603790000291
  • Figure BDA0005297603790000301
    Figure BDA0005297603790000301
Patent Text Reader

Abstract

Provided is a steel sheet which has a prescribed chemical composition and has a metallographic structure comprising, in area ratio, 80-95% of ferrite, 5-20% of martensite, and 0-10% in total of at least one of bainite, pearlite and retained austenite, and which is characterized in that the average particle spacing of the martensite is 2.5 [mu] m or less, and the average particle spacing of the martensite is 2.5 [mu] m or less. And the standard deviation in the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction is 1.5% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a steel sheet, and more specifically, to a steel sheet having a tensile strength of 400 MPa or more and excellent in appearance, mainly used for, for example, an outer panel member of an automobile. Background Art

[0002] In order to suppress the emission of carbon dioxide from automobiles, attempts have been made to use high-strength steel plates to ensure safety and to lighten the automobile body. Such high-strength steel plates for automobiles have made significant progress in automobile frame parts, but steel plates with a strength grade of less than 300MPa in terms of tensile strength are mainly used in outer plate components such as doors and engine hoods, and there has been no progress in high-strength. For such outer plate components, high formability and appearance are required. Generally speaking, if the strength of the steel plate is increased, the formability and appearance after forming are reduced. Therefore, in high-strength steel plates, it is difficult to take into account strength, formability and appearance, especially the appearance after forming. In the past, several solutions have been proposed to solve these problems.

[0003] For example, Patent Document 1 describes a hot-dip galvanized steel sheet, which is characterized in that it contains, by mass%, C: 0.02-0.3%, Si: 0.1-2.0%, Mn: less than 1.0%, Cr: more than 1.0-3.0%, P: less than 0.02%, S: less than 0.02%, Al: less than 0.014%, N: 0.001-0.008%, and satisfies 2.5≤1.5Mn%+Cr%, 4.1-2.3Mn%-1.2Cr%≤Si%, and the remainder is composed of Fe and inevitable impurities. In addition, Patent Document 1 teaches that by optimizing the addition amounts of Mn, Cr, and Si, it is possible to achieve both the workability and the appearance after work of a hot-dip galvanized steel sheet with a tensile strength of more than 390 MPa. Furthermore, Patent Document 1 also teaches that by setting the area ratio of ferrite as the main phase to 70% or more and the area ratio of the hard second phase including martensite to 30% or less, all of the strength, yield strength, yield ratio, and strength-ductility balance can be set to a good range.

[0004] A cold-rolled steel sheet is described in Patent Document 2, which is characterized in that it has the following composition by mass%: C: 0.0005 to 0.01%, Si: 0.2% or less, Mn: 0.1 to 1.5%, P: 0.03% or less, S: 0.005 to 0.03%, Ti: 0.02 to 0.1%, Al: 0.01 to 0.05%, N: 0.005% or less, Sb: 0.03% or less, Cu: more than 0.005% and 0.03% or less, and in the range where 0 < Ti* < 0.02, and further in the range where (Sb%) ≥ (Cu%) / 5, it contains Ti* represented by Ti* = (Ti%) - 3.4×(N%) - 1.5×(S%) - 4×(C%). The balance is composed of Fe and inevitable impurities. And, on both sides of the steel sheet, the content (mass%) of Ti element contained in precipitates with a size less than 20 nm in the plate thickness surface layer part from each surface to 10 μm is 9% or less of the total Ti content (mass%) in the steel sheet. In addition, Patent Document 2 teaches that by setting the content (mass%) of Ti element contained in precipitates with a size less than 20 nm in the plate thickness surface layer part from each surface of both sides of the steel sheet to 10 μm to 9% or less of the total Ti content (mass%) in the steel sheet, the occurrence of appearance unevenness due to such fine Ti-based precipitates can be avoided, and a cold-rolled steel sheet with excellent surface properties can be obtained; furthermore, this cold-rolled steel sheet can be suitably used in components that require excellent surface quality after forming, such as the outer panel of an automobile.

[0005] Prior Art Documents

[0006] Patent Documents

[0007] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2009-249737

[0008] Patent Document 2: WO 2011 / 142473 Summary of the Invention

[0009] Problems to be Solved by the Invention

[0010] For example, in the case of a composite structure steel having a metal structure including soft ferrite and hard martensite as described in Patent Document 1, it is easy to cause uneven deformation in which the soft ferrite and its surroundings are preferentially deformed during processing such as press forming. Therefore, in the case of using such a composite structure steel composed of soft structure and hard structure, due to the generation of tiny bumps and depressions on the surface of the steel plate after forming, a poor appearance called ghost line sometimes occurs. In connection with this, for example, in Patent Document 1, although the improvement of formability and appearance after forming is studied mainly from the perspective of chemical composition, sufficient research may not be conducted from the perspective of making the metal structure suitable. Therefore, with respect to the steel plates of the prior art, there is still room for improvement in terms of the improvement of formability and appearance after forming.

[0011] Therefore, an object of the present invention is to provide a steel sheet that can achieve a balance between strength, formability, and appearance after forming by a novel structure.

[0012] Means for solving problems

[0013] In order to achieve the above-mentioned object, the present inventors have conducted research focusing on the distribution state of martensite in addition to optimizing the ratio of the hard structure, i.e., martensite, in the metal structure. As a result, the present inventors have found that by uniformly dispersing the martensite contained in the metal structure at a predetermined ratio in both the microscopic region and the macroscopic region in the metal structure, the desired high strength and formability can be achieved based on such a hard structure, and even when strain is imparted by press forming, the generation of microscopic irregularities on the surface of the steel sheet can be significantly suppressed, thereby completing the present invention.

[0014] The gist of the present invention is as follows.

[0015] (1) A steel sheet having the following chemical composition in mass %:

[0016] C: 0.03~0.08%,

[0017] Si: 0.01-1.00%,

[0018] Mn: 0.50~3.00%,

[0019] P: 0.1000% or less,

[0020] S: 0.0200% or less,

[0021] Al: 1.000% or less,

[0022] N: 0.0200% or less,

[0023] O: 0~0.020%,

[0024] Cr: 0~2.000%,

[0025] Mo: 0~1.000%,

[0026] Ti: 0~0.500%,

[0027] Nb: 0~0.500%,

[0028] B: 0~0.0100%,

[0029] Cu: 0~1.000%,

[0030] Ni: 0-1.00%,

[0031] W: 0~0.100%、

[0032] V: 0~1.000%、

[0033] Ta: 0~0.100%、

[0034] Co: 0~3.000%,

[0035] Sn: 0~1.000%,

[0036] Sb: 0~0.500%,

[0037] As: 0~0.050%,

[0038] Mg: 0~0.050%,

[0039] Zr: 0~0.050%,

[0040] Ca: 0~0.0500%,

[0041] Y: 0~0.0500%、

[0042] La: 0~0.0500%,

[0043] Ce: 0~0.0500%,

[0044] Bi: 0 to 0.0500%, and

[0045] The rest: consists of Fe and impurities;

[0046] The steel plate has the following metal structure:

[0047] The area ratio is composed of the following:

[0048] Ferrite: 80-95%,

[0049] Martensite: 5-20%, and

[0050] At least one of bainite, pearlite and retained austenite: 0-10% in total,

[0051] Furthermore, the average particle spacing of martensite is less than 2.5 μm.

[0052] The standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the sheet thickness direction is 1.5% or less.

[0053] (2) The steel sheet according to (1) above, wherein the chemical composition contains at least one of the following elements in terms of mass %:

[0054] Cr: 0.001~2.000%,

[0055] Mo: 0.001~1.000%,

[0056] Ti: 0.001~0.500%,

[0057] Nb: 0.001~0.500%,

[0058] B: 0.0001~0.0100%,

[0059] Cu: 0.001~1.000%,

[0060] Ni: 0.001~1.00%,

[0061] W: 0.001~0.100%,

[0062] V: 0.001~1.000%,

[0063] Ta: 0.001~0.100%,

[0064] Co: 0.001~3.000%,

[0065] Sn: 0.001~1.000%,

[0066] Sb: 0.001~0.500%,

[0067] As: 0.001~0.050%,

[0068] Mg: 0.0001~0.050%,

[0069] Zr: 0.0001~0.050%,

[0070] Ca: 0.0001~0.0500%,

[0071] Y: 0.0001~0.0500%,

[0072] La: 0.0001~0.0500%,

[0073] Ce: 0.0001~0.0500% and

[0074] Bi: 0.0001~0.0500%.

[0075] Effects of the Invention

[0076] According to the present invention, it is possible to provide a steel sheet that can achieve a balance between strength, formability, and appearance after forming. DETAILED DESCRIPTION

[0077] <Steel Plate>

[0078] The steel sheet according to the embodiment of the present invention is characterized in that it has the following chemical composition in mass %:

[0079] C: 0.03~0.08%,

[0080] Si: 0.01-1.00%,

[0081] Mn: 0.50~3.00%,

[0082] P: 0.1000% or less,

[0083] S: 0.0200% or less,

[0084] Al: 1.000% or less,

[0085] N: 0.0200% or less,

[0086] O: 0~0.020%,

[0087] Cr: 0~2.000%,

[0088] Mo: 0~1.000%,

[0089] Ti: 0~0.500%,

[0090] Nb: 0~0.500%,

[0091] B: 0~0.0100%,

[0092] Cu: 0~1.000%,

[0093] Ni: 0-1.00%,

[0094] W: 0~0.100%、

[0095] V: 0~1.000%、

[0096] Ta: 0~0.100%、

[0097] Co: 0~3.000%,

[0098] Sn: 0~1.000%,

[0099] Sb: 0~0.500%,

[0100] As: 0~0.050%,

[0101] Mg: 0~0.050%,

[0102] Zr: 0~0.050%,

[0103] Ca: 0~0.0500%,

[0104] Y: 0~0.0500%、

[0105] La: 0~0.0500%,

[0106] Ce: 0~0.0500%,

[0107] Bi: 0 to 0.0500%, and

[0108] The rest: consists of Fe and impurities;

[0109] The steel plate has the following metal structure:

[0110] The area ratio is composed of the following:

[0111] Ferrite: 80-95%,

[0112] Martensite: 5-20%, and

[0113] At least one of bainite, pearlite and retained austenite: 0-10% in total,

[0114] Furthermore, the average particle spacing of martensite is less than 2.5 μm.

[0115] The standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the sheet thickness direction is 1.5% or less.

[0116] In the outer panel components such as car doors and engine hoods, composite structure steel (DP steel) with relatively low yield strength is often used from the viewpoint of avoiding surface defects called surface strain generated during press forming. However, in the case of DP steel in which a soft structure composed of ferrite and a hard structure composed of martensite are mixed, it is sometimes easy to cause uneven deformation of the soft structure and its surroundings during press forming and other processing, resulting in tiny bumps and depressions on the surface of the steel plate after forming, thereby producing a poor appearance called ghost lines. If described in more detail, during press forming and other processing, the soft structure composed of ferrite is deformed to a large extent, while the hard structure composed of martensite is deformed to a small extent. Therefore, the hard structure is not depressed compared with the soft structure, but is raised in a convex manner. As a result, the uneven deformation is generated in the width direction of the steel plate, especially in a band-shaped (striped) ghost line. On the other hand, with the high strength of the steel plate, in order to improve the hardenability of the steel plate, sometimes more elements such as Mn are added. Mn is an element that is easy to segregate in stripes in steel plates. More specifically, Mn concentrated areas such as central segregation and microsegregation are formed during casting. The concentrated areas are extended along the rolling direction by hot rolling or cold rolling, so that Mn segregates in stripes. Therefore, due to such segregation of Mn, there are areas with high hardenability and areas with low hardenability in the steel plate. As a result, a relatively large number of stripe-shaped hard structures are generated in the metal structure of the steel plate after quenching. In this case, the generation of ghost lines becomes particularly significant. In contrast, if the segregation of Mn in the steel plate can be fully suppressed, the generation of such stripe-shaped hard structures can be reduced and the hard structures can be more evenly dispersed in the metal structure. It is believed that in this case, even if strain is given by press forming, the generation of micro-concave and convex in the surface of the steel plate can be fully reduced, and the generation of ghost lines can be suppressed. However, with the demand for high strength, especially when the amount of Mn added in the steel plate increases, it is actually very difficult to reliably and fully suppress the segregation of Mn. Furthermore, as the strength increases, the formability itself decreases, and therefore it is generally very difficult to achieve a balance between strength, formability, and appearance after forming.

[0117] Therefore, first, the present inventors studied the following scheme: by optimizing the chemical composition of the steel sheet and optimizing the ratio of the soft structure, i.e., ferrite, to the hard structure, i.e., martensite, in the metal structure, to achieve the desired high strength and formability, and on the other hand, further improve the appearance after forming. Specifically, the present inventors focused on the distribution state of the hard structure, i.e., martensite, in the metal structure, and more specifically, studied the control of the distribution of martensite from another point of view different from the reduction of Mn segregation. As a result, as described in detail below in the method for manufacturing the steel sheet, the present inventors found that by constituting the metal structure of the steel sheet before the final annealing with bainite and / or martensite, and then performing the final annealing on the steel sheet having such a metal structure under predetermined conditions, it is not necessarily dependent on the presence or absence and degree of Mn segregation, and it is possible to uniformly disperse martensite in both the microscopic region and the macroscopic region in the final metal structure. More specifically, the inventors have found that by performing final annealing on a steel sheet having a metal structure composed of bainite and / or martensite under prescribed conditions, the average particle spacing of martensite can be controlled to be less than 2.5 μm in the microscopic region, and the standard deviation in the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction can be controlled to be less than 1.5% in the macroscopic region. By controlling the average particle spacing of martensite to be less than 2.5 μm, the hard structure can be made dense and uniformly dispersed in the microscopic region. By controlling the standard deviation in the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction to be less than 1.5%, the unevenness of the hard structure in the macroscopic region can be significantly reduced. By satisfying these two requirements, a metal structure in which the hard structure, i.e., martensite, is finely and uniformly dispersed in the entire steel sheet can be formed. As a result, according to the steel sheet of the embodiment of the present invention, even when forming such as press forming, the deformation amount of the steel sheet can be made more uniform, especially in the width direction, and an excellent appearance after forming can be achieved, which significantly suppresses appearance defects such as ghost lines. For example, even if the uniformity of martensite in the microscopic region is ensured, if the uniformity of martensite in the macroscopic region is not ensured, a metal structure in which martensite is finely and evenly dispersed in the entire steel plate cannot be formed. Similarly, even if the uniformity of martensite in the macroscopic region is ensured, if the uniformity of martensite in the microscopic region is not ensured, a metal structure in which martensite is finely and evenly dispersed in the entire steel plate cannot be formed because martensite may become locally non-uniform. Therefore, in the steel plate of the embodiment of the present invention, in order to achieve an excellent post-forming appearance in which appearance defects such as ghost lines are significantly suppressed, it becomes necessary to meet the following two requirements: the average particle spacing of martensite is controlled to be less than 2.5μm, and the standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction is controlled to be less than 1.5%.

[0118] Although it is not intended to be bound by any particular theory, it is believed that in order to make martensite finely and evenly dispersed in the entire steel plate in the metal structure of the steel plate finally obtained, it is extremely important to form a large number of austenite nucleation sites in a highly dispersed manner during heating in the final annealing. In association with it, the martensitic structure further has lower structures such as lath bundles, lath blocks, and laths in the original austenite grains, so it is a structure with a large number of various interfaces inside compared to structures such as ferrite. Bainite is also a structure with a large number of various interfaces inside, just like the case of martensite. Therefore, by constituting the metal structure in the steel plate before the final annealing by bainite and / or martensite, it becomes possible to disperse and generate carbides that can become nucleation sites of austenite on these interfaces in large quantities at the stage of heating such a metal structure in the final annealing. Therefore, it is believed that after generating a large number of carbides on the interface, the temperature is further heated to the 2-phase domain of ferrite and austenite, and austenite can be generated finely and evenly in the entire steel plate. Finally, by quenching the steel plate having such a metal structure, martensite is generated from these austenites, so that in the final metal structure, the average particle spacing of martensite is controlled to be less than 2.5μm, and the standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction is controlled to be less than 1.5%. That is, it is believed that a metal structure in which martensite is uniformly dispersed in both the microscopic region and the macroscopic region can be obtained. It is believed that by implementing such a heat treatment, the martensite can be finely and uniformly dispersed in the entire steel plate to the extent that the influence of Mn segregation is eliminated. In the past, from the perspective of reducing Mn segregation itself, it was generally considered to study the distribution control of hard structure. Therefore, it is not necessarily dependent on the presence or absence of Mn segregation, the degree, and the fact that martensite can be uniformly dispersed in both the microscopic region and the macroscopic region in the final metal structure is extremely unexpected and shocking.

[0119] According to the steel sheet of the embodiment of the present invention, in addition to the above-mentioned understanding, good formability can be ensured by controlling the area ratio of the soft structure, i.e., ferrite, to 80-95%, and by controlling the area ratio of the hard structure, i.e., martensite, to 5-20%, and further controlling the chemical composition of the steel sheet to a prescribed range, a high strength of 400 MPa or more in tensile strength can be ensured. As a result, it is possible to achieve a balance between strength, formability, and appearance after forming at a high level. The following is a more detailed description of the various components of the steel sheet of the embodiment of the present invention.

[0120] First, the metal structure of the steel plate according to the embodiment of the present invention is described. Hereinafter, the structure fraction is expressed as an area ratio, so the unit "%" of the structure fraction refers to area%. In addition, as described below, the metal structure is controlled at the 1 / 4 portion of the plate thickness of the steel plate. The 1 / 4 portion of the plate thickness of the steel plate refers to the area between the surface at a depth of 1 / 8 of the plate thickness and the surface at a depth of 3 / 8 of the plate thickness from the rolled surface of the steel plate. Hereinafter, unless otherwise specified, the structure fraction refers to the value at the 1 / 4 portion of the plate thickness.

[0121] [Ferrite: 80-95%]

[0122] Since ferrite is a soft structure, it is easy to deform and helps to improve the elongation. If the area ratio of ferrite is 80% or more, sufficient formability can be obtained. From the viewpoint of improving formability, the higher the area ratio of ferrite, the more preferred it is, for example, it can also be 82% or more, 85% or more, 87% or more, or 90% or more. On the other hand, if ferrite is excessively contained, the desired strength may not be achieved in the steel plate. Therefore, the area ratio of ferrite is set to 95% or less. The area ratio of ferrite may also be 94% or less or 92% or less.

[0123] [Martensite: 5-20%]

[0124] Since martensite is a hard structure with high dislocation density, it is a structure that helps to improve the tensile strength. By setting the area ratio of martensite to 5% or more, a tensile strength of 400MPa or more can be ensured. From the viewpoint of improving strength, the higher the area ratio of martensite, the more preferred it is, for example, it can also be 7% or more, 10% or more, or 13% or more. On the other hand, if the area ratio of martensite is 20% or less, formability and appearance can be ensured. The area ratio of martensite can also be 17% or less or 15% or less. In the present invention, "martensite" includes not only quenched martensite (so-called primary martensite), but also tempered martensite.

[0125] [At least one of bainite, pearlite and retained austenite: 0 to 10% in total]

[0126] The remaining structure other than ferrite and martensite can also be calculated as 0% by area ratio, but in the case of the presence of the remaining structure, the remaining structure is at least one of bainite, pearlite and retained austenite. From the viewpoint of ensuring the above-mentioned effects based on ferrite and martensite, the area ratio of the remaining structure, i.e., at least one of bainite, pearlite and retained austenite, is set to a total of less than 10%, for example, less than 8%, less than 6%, less than 4%, less than 3% or less than 2%. In particular, the area ratio of retained austenite can also be 0 to 3%. For example, the area ratio of retained austenite can also be less than 2%, less than 1%, less than 0.5%, less than 0.3% or less than 0.1%. On the other hand, in order to set the area ratio of the remaining structure to 0%, a high degree of control is required in the manufacturing process of the steel plate, which sometimes leads to a reduction in the yield. Therefore, the area ratio of the remaining structure can also be more than 0.5% or more than 1%.

[0127] [Identification of metal structure and calculation of area ratio]

[0128] The identification of the metal structure and the calculation of the area ratio are carried out by using FE-SEM (field emission scanning electron microscope, such as JSM-7200F manufactured by JEOL, measured at an accelerating voltage of 15 kV) after corrosion with nital or Lepera solution, an optical microscope, and X-ray diffraction. The structural observation using FE-SEM and an optical microscope is carried out at a magnification of 1000 to 50,000 times on a 100 μm × 100 μm area in the cross section of the steel plate in a direction parallel to the rolling direction and perpendicular to the plate surface. For any metal structure, the measurement site is set to 3, and the area ratio is determined by calculating the average value of these measurement values. For example, in the case where a measurement area of ​​100 μm cannot be ensured in the thickness direction due to the thin thickness of the steel plate to be measured, the length in the thickness direction is reduced and a measurement area of ​​10,000 μm is ensured. 2 . For example, a measurement area of ​​20 μm in the plate thickness direction and 500 μm in the rolling direction may be set as the observation object. However, if the number of grains contained in the plate thickness direction becomes too small, the measurement accuracy may be reduced. Therefore, the measurement length in the plate thickness direction is set to be greater than 10 μm, preferably greater than 50 μm. The same applies to the "100 μm×100 μm area" in the following description.

[0129] The area ratio of ferrite is obtained by observing a 100 μm×100 μm region ranging from the 1 / 8 position to the 3 / 8 position of the plate thickness with the 1 / 4 position of the plate thickness as the center in an electron channel contrast image using FE-SEM (field emission scanning electron microscope). More specifically, it can be calculated by image analysis using image analysis software Image J.

[0130] The area ratio of martensite is obtained by the following steps. First, the observation surface of the sample is corroded with Lepera liquid, and then the area of ​​100μm×100μm is observed with FE-SEM within the range of 1 / 8 position to 3 / 8 position of the plate thickness centered on the 1 / 4 position of the plate thickness. In Lepera corrosion, since martensite and retained austenite are not corroded, the area ratio of the uncorroded area corresponds to the total area ratio of martensite and retained austenite. Specifically, using the image analysis software Image J, the metal structure is binarized by the difference in brightness, the black part of the image data is ferrite, and the white part that is not corroded by Lepera is the total structure of martensite and retained austenite. Therefore, the area ratio of martensite is calculated by subtracting the area ratio of retained austenite measured by the X-ray diffraction method described later from the area ratio of the uncorroded area. The area ratio of martensite obtained by this method also includes the area ratio of tempered martensite.

[0131] The area ratio of retained austenite is calculated by X-ray diffraction. First, the sample is removed by mechanical grinding and chemical grinding from the plate surface to the depth 1 / 4 position in the plate thickness direction. Then, at the 1 / 4 position of the plate thickness, the structural fraction of retained austenite is calculated by the integrated intensity ratio of the diffraction peaks of (200) and (211) of the bcc phase and (200), (220) and (311) of the fcc phase obtained using MoKα rays. As the calculation method, the general 5-peak method is used. The calculated structural fraction of retained austenite is determined as the area ratio of retained austenite.

[0132] The identification of bainite and the calculation of the area ratio are carried out by the following steps. First, the observation surface of the sample is corroded with nitric acid, and then the area of ​​100μm×100μm is observed with FE-SEM in the range of 1 / 8 position to 3 / 8 position of the plate thickness centered on the 1 / 4 position of the plate thickness. In this observation area, bainite is identified by the position of cementite contained in the structure and the arrangement of cementite as follows. Bainite is classified into upper bainite and lower bainite, and the upper bainite has cementite or residual austenite at the interface of lath-shaped bainitic ferrite. The lower bainite has cementite inside the lath-shaped bainitic ferrite, and the crystal orientation relationship between bainitic ferrite and cementite is one, and the cementite has the same variant. Based on these characteristic points, the upper bainite and the lower bainite can be identified separately. In the present invention, they are collectively referred to as bainite, and the area ratio of the identified bainite is calculated based on image analysis. It should be noted that cementite is observed as a region with high brightness on the SEM image. By analyzing the chemical composition using Energy Dispersive X-ray Spectroscopy (EDS), cementite can be confirmed to be a carbonitride mainly composed of iron.

[0133] The identification of pearlite and the calculation of the area ratio are carried out by the following steps. First, the observation surface of the sample is corroded with nitric acid, and then the range of the plate thickness position from 1 / 8 position to 3 / 8 position centered on the plate thickness position of 1 / 4 is observed with an optical microscope. The observation image of the optical microscope is binarized by the difference in brightness, and the area where the black part and the white part are dispersed in a lamellar manner is identified as pearlite, and the area ratio of the area is calculated based on image analysis. More specifically, the image analysis software Image J is used to binarize by the difference in brightness, and an image taken with a measurement magnification of 500 times containing a shooting range of 100μm×100μm is used to obtain the area fraction of pearlite by the point counting method. Within the above shooting range, 8 lines can be drawn at equal intervals parallel to the rolling direction and 8 lines can be drawn at equal intervals perpendicular to the rolling direction, and the proportion of pearlite in the 64 intersections formed by these lines is calculated as the area fraction of pearlite.

[0134] [Average particle spacing of martensite: 2.5 μm or less]

[0135] In an embodiment of the present invention, the average particle spacing of the hard structure, i.e., martensite, is controlled to be less than 2.5 μm. The average particle spacing of martensite is an indicator of the uniformity of the hard structure distribution in the microscopic area. The smaller the average particle spacing of martensite, the denser and more evenly dispersed the hard structure is, so it can be said that the uniformity is higher. Regarding the appearance of the steel plate after press forming, the more uniform the deformation of the steel plate during press forming, especially in the width direction of the steel plate, the better it becomes. Since the deformation of the steel plate is strongly affected by the distribution state of the hard structure, in order to make the deformation of the steel plate uniform in the width direction of the steel plate, it is necessary to make the distribution of the hard structure in the metal structure uniform. In addition to the control of the standard deviation in the area ratio of martensite described later, the average particle spacing of martensite is controlled to be less than 2.5 μm, so that the deformation of the steel plate can be made more uniform in the width direction even during press forming, and as a result, a good appearance after forming can be achieved. The average particle spacing of martensite is preferably 2.4 μm or less, more preferably 2.2 μm or less, and most preferably 2.0 μm or less or 1.8 μm or less. The lower limit is not particularly limited, but for example, the average particle spacing of martensite may be 0.5 μm or more, 0.8 μm or more, or 1.0 μm or more.

[0136] [Measurement of average particle spacing of martensite]

[0137] The average particle spacing of martensite is determined as follows. First, a sample of a steel plate cross section having a direction parallel to the rolling direction and perpendicular to the plate surface is collected, and the cross section is used as an observation surface. In the observation surface, a 100μm×100μm area within the range of 1 / 8 position to 3 / 8 position of the plate thickness centered on the 1 / 4 position of the plate thickness is set as the observation area, and FE-SEM is used to identify martensite. Specifically, the image analysis software Image J is used to binarize the metal structure by the difference in brightness to identify martensite. In the case of using Lepera liquid, the black part of the image data is ferrite, and the white part that is not corroded by Lepera is the combined structure of martensite and retained austenite. However, in the steel plate of the embodiment of the present invention, since the area ratio of retained austenite is sufficiently low compared to the area ratio of martensite, the white structure can be regarded as martensite. Next, based on image analysis, the distance between the centers (centers of gravity) of all adjacent martensite grains in the identified martensite is calculated as the particle spacing, and the average value of the calculated particle spacing is determined as the average particle spacing of the martensite (strictly speaking, particles containing martensite and / or retained austenite).

[0138] [Standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction is 1.5% or less]

[0139] In an embodiment of the present invention, the standard deviation in the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction is controlled to be less than 1.5%. The standard deviation is an index indicating the uniformity of the hard structure in the macro region. The appearance that becomes a problem during press forming depends on the tiny bumps on the surface of the steel plate caused by the difference in the amount of deformation in the width direction of the steel plate. Therefore, if the unevenness in the area ratio of the hard structure contained in the plate thickness in the direction perpendicular to the rolling direction and the plate thickness direction is large, the amount of deformation in the width direction of the steel plate will be different, and as a result, tiny bumps will be generated on the surface of the steel plate. Therefore, it is effective to reduce the standard deviation in the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction, that is, the width direction of the steel plate. More specifically, by controlling the standard deviation to be less than 1.5% in addition to the control of the average particle spacing of martensite described above, the unevenness in the amount of deformation in the width direction of the steel plate can be further reduced even during press forming, and as a result, a good appearance after forming can be achieved. The standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction is preferably 1.4% or less, more preferably 1.2% or less, and most preferably 1.0% or less. The lower limit is not particularly limited, but for example, the standard deviation may be 0.1% or more, 0.3% or more, or 0.5% or more.

[0140] [Measurement of Standard Deviation of Area Ratio of Martensite in Directions Perpendicular to Rolling Direction and Plate Thickness Direction]

[0141] The standard deviation in the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction is determined as follows. First, obtain a metal structure image in the cross section of the steel plate in an area of ​​50 mm in the direction perpendicular to the rolling direction. In the case of an image of 10 mm or smaller, multiple images can also be obtained, and their total is set to 50 mm. Next, the obtained image is divided into 100 μm (0.1 mm) each in the direction perpendicular to the rolling direction, and the area ratio of martensite in the entire plate thickness is calculated in each divided range. Based on the martensite area ratio calculated from a total of 500 divided images, the standard deviation in the area ratio of martensite is calculated. This operation is performed on three areas with different positions in the rolling direction, and the average value of the standard deviations respectively obtained is determined as the standard deviation in the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction.

[0142] When the rolling direction of the steel plate is unclear, the following method is used as a method for determining the rolling direction of the steel plate. After the plate thickness section of the steel plate is finished by mirror polishing, the S concentration is measured using an electron probe microanalyzer (EPMA, Electron Probe Micro Analyzer). The measurement conditions are to set the acceleration voltage to 15kV, set the measurement interval to 1μm, and measure the distribution image of a 500μm square range in the center of the plate thickness. At this time, the extended area with a high S concentration is judged as an inclusion such as MnS. It can also be observed in multiple fields of view during observation. Next, using the plate thickness section observed for the first time by the above method as a reference, the surface that becomes parallel to the surface rotated every 5° in the range of 0° to 180° with the plate thickness direction as the axis is observed in section by the above method. For each section, the average value of the length of the major axis of multiple inclusions in each section is calculated, and the section where the average value of the length of the major axis of the inclusion becomes the largest is determined. The direction in the section parallel to the major axis direction of the inclusion is judged as the rolling direction. For example, if the steel plate to be measured is too thin to ensure a measurement area of ​​500 μm square, the length in the plate thickness direction is reduced to ensure a measurement area of ​​250,000 μm square. 2 .

[0143] Next, the reasons for limiting the chemical composition of the steel sheet according to the embodiment of the present invention will be described. Hereinafter, % related to the chemical composition means mass %.

[0144] [C: 0.03~0.08%]

[0145] C is an element that ensures a predetermined amount of martensite and improves the strength of the steel sheet. In order to fully obtain such an effect, the C content is set to 0.03% or more. The C content may also be 0.04% or more or 0.05% or more. On the other hand, if excessive C is contained, the strength may become too high and the elongation may decrease. Therefore, the C content is set to 0.08% or less. The C content may also be 0.07% or less or 0.06% or less.

[0146] [Si: 0.01~1.00%]

[0147] Si is an element that improves the strength of the steel plate by solid solution strengthening. In order to fully obtain such an effect, the Si content is set to 0.01% or more. The Si content can also be 0.05% or more, 0.10% or more, 0.20% or more, 0.30% or more, or 0.40% or more. On the other hand, if Si is excessively contained, it is sometimes difficult to remove the oxide scale generated during hot rolling, resulting in deterioration of the appearance. Therefore, the Si content is set to 1.00% or less. The Si content can also be 0.90% or less, 0.80% or less, 0.70% or less, or 0.60% or less.

[0148] [Mn: 0.50~3.00%]

[0149] Mn is an element that improves hardenability and contributes to the improvement of steel plate strength. In order to fully obtain such an effect, the Mn content is set to 0.50% or more. The Mn content can also be 0.70% or more, 1.00% or more, 1.20% or more, or 1.50% or more. In the preferred manufacturing method of the steel plate described later, in order to make the martensite uniformly dispersed in both the microscopic region and the macroscopic region in the final metal structure, it is necessary to constitute the metal structure in the steel plate before the final annealing by bainite and / or martensite. Therefore, the improvement of hardenability brought about by the addition of Mn can also be said to be important in improving the appearance after forming. On the other hand, if Mn is excessively contained, the ferrite phase transformation is sometimes excessively suppressed, the desired amount of ferrite cannot be ensured, and the elongation is reduced. Therefore, the Mn content is set to 3.00% or less. The Mn content can also be 2.80% or less, 2.50% or less, 2.20% or less, or 2.00% or less.

[0150] [P: 0.1000% or less]

[0151] P is an impurity element, which is an element that makes the weld brittle and deteriorates the platability. Therefore, the P content is set to 0.1000% or less. The P content can also be 0.0600% or less, 0.0200% or less, 0.0150% or less, or 0.0100% or less. The lower the P content, the better. The lower limit is not particularly limited and can also be 0%. On the other hand, if the P content is reduced to less than 0.0001% in practical steel plates, the manufacturing cost will increase significantly, which will become economically disadvantageous. Therefore, the P content can also be more than 0.0001%, more than 0.0002%, or more than 0.0005%.

[0152] [S: 0.0200% or less]

[0153] S is an impurity element that hinders weldability and also hinders manufacturability during casting and hot rolling. Therefore, the S content is set to 0.0200% or less. The S content may also be 0.0150% or less, 0.0120% or less, 0.0100% or less, or 0.0080% or less. The lower the S content, the better. The lower limit is not particularly limited and may also be 0%. On the other hand, if the S content is reduced to less than 0.0001% in practical steel plates, the manufacturing cost will increase significantly, which becomes economically disadvantageous. Therefore, the S content may also be 0.0001% or more, 0.0002% or more, or 0.0005% or more.

[0154] [Al: 1.000% or less]

[0155] Al is an element that functions as a deoxidizer and is an effective element for improving the strength of steel. The Al content may be 0%, but in order to fully obtain these effects, the Al content is preferably 0.001% or more. The Al content may also be 0.005% or more, 0.010% or more, 0.025% or more, or 0.050% or more. On the other hand, if Al is excessively contained, coarse oxides are sometimes formed, which reduces toughness. Therefore, the Al content is set to 1.000% or less. The Al content may also be 0.800% or less, 0.600% or less, or 0.300% or less.

[0156] [N: 0.0200% or less]

[0157] N is an element that causes pores during welding. Therefore, the N content is set to 0.0200% or less. The N content may also be 0.0180% or less, 0.0150% or less, 0.0100% or less, 0.0080% or less, or 0.0060% or less. The lower the N content, the better. The lower limit is not particularly limited and may also be 0%. On the other hand, if N is reduced to less than 0.0001% in practical steel plates, the manufacturing cost will increase significantly, which will be economically disadvantageous. Therefore, the N content may also be 0.0001% or more, 0.0002% or more, or 0.0005% or more.

[0158] [O: 0~0.020%]

[0159] O is an element that causes pores during welding. Therefore, the O content is set to 0.020% or less. The O content may also be 0.018% or less, 0.015% or less, 0.010% or less, or 0.008% or less. The lower the O content, the better. The lower limit is not particularly limited and may also be 0%. On the other hand, if O is reduced to less than 0.0001% in practical steel plates, the manufacturing cost will increase significantly, which will be economically disadvantageous. Therefore, the O content may also be 0.0001% or more, 0.0002% or more, or 0.0005% or more.

[0160] The basic chemical composition of the steel plate according to the embodiment of the present invention is as described above. Furthermore, the steel plate may contain at least one of the following optional elements to replace a part of the remaining Fe for the purpose of improving properties as needed. For example, the steel plate may contain Cr: 0 to 2.000%, Mo: 0 to 1.000%, Ti: 0 to 0.500%, Nb: 0 to 0.500%, B: 0 to 0.0100%, Cu: 0 to 1.000%, Ni: 0 to 1.00%, W: 0 to 0.100%, V: 0 to 1.000%, Ta: 0 to 0.100%, Co: 0 to 3. At least one of: 0.000%, Sn: 0 to 1.000%, Sb: 0 to 0.500%, As: 0 to 0.050%, Mg: 0 to 0.050%, Zr: 0 to 0.050%, Ca: 0 to 0.0500%, Y: 0 to 0.0500%, La: 0 to 0.0500%, Ce: 0 to 0.0500% and Bi: 0 to 0.0500%. These optional elements are described in detail below.

[0161] [Cr: 0~2.000%]

[0162] Cr is an element that improves hardenability and contributes to the improvement of steel plate strength in the same way as Mn. The Cr content may be 0%, but in order to obtain the above-mentioned effect, the Cr content is preferably 0.001% or more. The Cr content may also be 0.010% or more, 0.100% or more, or 0.200% or more. On the other hand, even if Cr is excessively contained, the effect is saturated, which may lead to an increase in manufacturing costs. Therefore, the Cr content is preferably 2.000% or less, and may also be 1.500% or less, 1.000% or less, or 0.500% or less.

[0163] [Mo: 0~1.000%]

[0164] Mo is an element that contributes to the high strength of the steel sheet in the same way as Cr. This effect can be obtained even in a trace amount. The Mo content may be 0%, but in order to obtain the above-mentioned effect, the Mo content is preferably 0.001% or more. The Mo content may also be 0.010% or more, 0.020% or more, 0.050% or more, or 0.100% or more. On the other hand, if Mo is excessively contained, hot workability may be reduced and productivity may be reduced. Therefore, the Mo content is preferably 1.000% or less. The Mo content may also be 0.800% or less, 0.400% or less, or 0.200% or less.

[0165] [Ti: 0~0.500%]

[0166] Ti is an element effective in controlling the morphology of carbides. Ti can promote the increase in the strength of ferrite. The Ti content can also be 0%, but in order to obtain these effects, the Ti content is preferably 0.001% or more. The Ti content can also be 0.002% or more, 0.010% or more, 0.020% or more, or 0.050% or more. On the other hand, even if Ti is excessively contained, the effect is saturated, which may lead to an increase in manufacturing costs. Therefore, the Ti content is preferably 0.500% or less, and can also be 0.400% or less, 0.200% or less, or 0.100% or less.

[0167] [Nb: 0~0.500%]

[0168] Nb is an element that is effective in controlling the morphology of carbides like Ti, and is also an element that is effective in improving the toughness of the steel plate by refining the structure. These effects can be obtained even in trace amounts. The Nb content can also be 0%, but in order to obtain the above-mentioned effects, the Nb content is preferably 0.001% or more. The Nb content can also be 0.005% or more or 0.010% or more. On the other hand, if Nb is excessively contained, coarse carbides and the like are sometimes generated in the steel, reducing the toughness of the steel plate. Therefore, the Nb content is preferably 0.500% or less. The Nb content can also be 0.200% or less, 0.100% or less, or 0.060% or less.

[0169] [B: 0~0.0100%]

[0170] B is an element that inhibits the formation of ferrite and pearlite and promotes the formation of martensite during the cooling process from austenite. In addition, B is an element that is beneficial to the high strength of steel. These effects can be obtained even in trace amounts. The B content can also be 0%, but in order to obtain the above-mentioned effects, the B content is preferably 0.0001% or more. The B content can also be 0.0005% or more or 0.0010% or more. On the other hand, if B is excessively contained, toughness and / or weldability sometimes decrease. Therefore, the B content is preferably 0.0100% or less. The B content can also be 0.0080% or less, 0.0050% or less, 0.0030% or less, or 0.0020% or less.

[0171] [Cu: 0~1.000%]

[0172] Cu is an element that contributes to the improvement of the strength of the steel plate. This effect can be obtained even in a trace amount. The Cu content may be 0%, but in order to obtain the above-mentioned effect, the Cu content is preferably 0.001% or more. The Cu content may also be 0.005% or more, 0.010% or more, or 0.050% or more. On the other hand, if excessive Cu is contained, red-hot brittleness may result and productivity in hot rolling may be reduced. Therefore, the Cu content is preferably 1.000% or less. The Cu content may also be 0.800% or less, 0.600% or less, 0.300% or less, or 0.100% or less.

[0173] [Ni: 0~1.00%]

[0174] Ni is an element effective in improving the strength of the steel plate. The Ni content may be 0%, but in order to obtain the above-mentioned effect, the Ni content is preferably 0.001% or more. The Ni content may also be 0.005% or more or 0.010% or more. On the other hand, if Ni is excessively contained, the weldability of the steel plate may be reduced. Therefore, the Ni content is preferably 1.00% or less. The Ni content may also be 0.80% or less, 0.40% or less, or 0.20% or less.

[0175] [W: 0~0.100%]

[0176] W is an element effective in controlling the morphology of carbides and improving the strength of steel sheets. The W content may be 0%, but in order to obtain these effects, the W content is preferably 0.001% or more. The W content may be 0.005% or more or 0.010% or more. On the other hand, if W is excessively contained, weldability may be reduced. Therefore, the W content is preferably 0.100% or less. The W content may also be 0.080% or less, 0.040% or less, or 0.020% or less.

[0177] [V: 0~1.000%]

[0178] V is an element that is effective in controlling the morphology of carbides like Ti and Nb, and is also an element that is effective in improving the toughness of the steel plate by refining the structure. The V content may be 0%, but in order to obtain the above-mentioned effect, the V content is preferably 0.001% or more. The V content may also be 0.005% or more, 0.010% or more, or 0.050% or more. On the other hand, if V is excessively contained, a large amount of precipitates may be generated, which may reduce the toughness. Therefore, the V content is preferably 1.000% or less. The V content may also be 0.400% or less, 0.200% or less, or 0.100% or less.

[0179] [Ta: 0~0.100%]

[0180] Ta is an element that is effective for controlling the morphology of carbides and improving the strength of steel sheets, similar to W. The Ta content may be 0%, but in order to obtain these effects, the Ta content is preferably 0.001% or more. The Ta content may also be 0.005% or more or 0.010% or more. On the other hand, even if Ta is excessively contained, the effect is saturated, and containing it in the steel sheet more than necessary will lead to an increase in manufacturing costs. Therefore, the Ta content is preferably 0.100% or less. The Ta content may also be 0.080% or less, 0.040% or less, or 0.020% or less.

[0181] [Co: 0~3.000%]

[0182] Co is an element that is effective in improving the strength of the steel plate, similarly to Ni. The Co content may be 0%, but in order to obtain the above-mentioned effect, the Co content is preferably 0.001% or more. The Co content may also be 0.005% or more, 0.010% or more, or 0.100% or more. On the other hand, if Co is excessively contained, hot workability may be reduced and the cost of raw materials may be increased. Therefore, the Co content is preferably 3.000% or less. The Co content may also be 2.000% or less, 1.000% or less, 0.500% or less, or 0.200% or less.

[0183] [Sn: 0~1.000%]

[0184] Sn is an element that may be contained in a steel sheet when scrap iron is used as a raw material of the steel sheet. In addition, Sn may cause embrittlement of ferrite. Therefore, the smaller the Sn content, the better, preferably 1.000% or less. The Sn content may also be 0.100% or less, 0.040% or less, or 0.020% or less. The Sn content may also be 0%, but reducing the Sn content to less than 0.001% will lead to an excessive increase in refining costs. Therefore, the Sn content may also be 0.001% or more, 0.005% or more, or 0.010% or more.

[0185] [Sb: 0~0.500%]

[0186] Sb is an element that may be contained in a steel sheet when using scrap iron as a raw material of the steel sheet, similarly to Sn. In addition, Sb may be strongly segregated at the grain boundary and cause embrittlement of the grain boundary. Therefore, the lower the Sb content, the better, preferably 0.500% or less. The Sb content may also be 0.100% or less, 0.040% or less, or 0.020% or less. The Sb content may also be 0%, but reducing the Sb content to less than 0.001% will lead to an excessive increase in refining costs. Therefore, the Sb content may also be 0.001% or more, 0.005% or more, or 0.010% or more.

[0187] [As: 0~0.050%]

[0188] As is an element that can be contained in the steel sheet when using scrap iron as the raw material of the steel sheet, similarly to Sn and Sb. In addition, As is an element that strongly segregates at the grain boundaries, and the less As content, the better. The As content is preferably 0.050% or less, and may be 0.040% or less or 0.020% or less. The As content may also be 0%, but reducing the As content to less than 0.001% will lead to an excessive increase in refining costs. Therefore, the As content may also be 0.001% or more, 0.005% or more, or 0.010% or more.

[0189] [Mg: 0~0.050%]

[0190] Mg controls the morphology of sulfides and oxides, and contributes to improving the bending formability of the steel sheet. This effect can be obtained even in a trace amount. The Mg content may be 0%, but in order to obtain the above effect, the Mg content is preferably 0.0001% or more. The Mg content may also be 0.0005% or more, 0.001% or more, or 0.005%. On the other hand, even if Mg is excessively contained, the effect is saturated, and containing more than necessary in the steel sheet will lead to an increase in manufacturing costs. Therefore, the Mg content is preferably 0.050% or less. The Mg content may also be 0.040% or less, 0.020% or less, or 0.010% or less.

[0191] [Zr: 0~0.050%]

[0192] Zr is an element that can control the form of sulfides in a trace amount. The Zr content may be 0%, but in order to obtain the above-mentioned effect, the Zr content is preferably 0.0001% or more. The Zr content may be 0.0005% or more, 0.001% or more, or 0.005% or more. On the other hand, even if Zr is excessively contained, the effect is saturated, and containing it in the steel sheet more than necessary will lead to an increase in manufacturing costs. Therefore, the Zr content is preferably 0.050% or less. The Zr content may also be 0.040% or less, 0.020% or less, or 0.010% or less.

[0193] [Ca: 0~0.0500%]

[0194] [Y: 0~0.0500%]

[0195] [La: 0~0.0500%]

[0196] [Ce: 0~0.0500%]

[0197] Ca, Y, La and Ce are elements that can control the form of sulfides in a trace amount. The content of Ca, Y, La and Ce may be 0%, but in order to obtain the above-mentioned effects, the content of Ca, Y, La and Ce is preferably 0.0001% or more, and may be 0.0005% or more, 0.0010% or more, 0.0020% or more, or 0.0030% or more. On the other hand, even if these elements are excessively contained, the effect is saturated, and containing them in the steel sheet more than necessary will lead to an increase in manufacturing costs. Therefore, the content of Ca, Y, La and Ce is preferably 0.0500% or less, and may be 0.0200% or less, 0.0100% or less, or 0.0060% or less.

[0198] [Bi: 0~0.0500%]

[0199] Bi is an element that improves formability by refining the solidification structure. The Bi content may be 0%, but in order to obtain such an effect, the Bi content is preferably 0.0001% or more, and may be 0.0005% or more, 0.0010% or more, or 0.0050% or more. On the other hand, even if Bi is excessively contained, the effect is saturated, and containing Bi in the steel sheet more than necessary will lead to an increase in manufacturing costs. Therefore, the Bi content is preferably 0.0500% or less, and may be 0.0400% or less, 0.0200% or less, or 0.0100% or less.

[0200] In the steel sheet of the embodiment of the present invention, the remainder other than the above elements is composed of Fe and impurities. Impurities are elements that are mixed from steel raw materials and / or during steelmaking and are allowed to exist within a range that does not hinder the characteristics of the steel sheet of the embodiment of the present invention.

[0201] The chemical composition of the steel sheet according to the embodiment of the present invention can be measured by a general analytical method. For example, the chemical composition of the steel sheet can be measured by using inductively coupled plasma emission spectrometry (ICP-AES). C and S can be measured by using a combustion-infrared absorption method, N can be measured by using an inert gas fusion-thermal conductivity method, and O can be measured by using an inert gas fusion-non-dispersive infrared absorption method.

[0202] [Plate thickness]

[0203] The steel plate of the embodiment of the present invention is not particularly limited, but has a plate thickness of 0.2 to 2.0 mm, for example. A steel plate having such a plate thickness is suitable when used as a raw material for a cover member such as a door or hood of an automobile. The plate thickness may be 0.3 mm or more or 0.4 mm or more. Similarly, the plate thickness may be 1.8 mm or less, 1.5 mm or less, 1.2 mm or less, or 1.0 mm or less. The plate thickness of the steel plate is measured by a micrometer.

[0204] [Plating]

[0205] The steel sheet of the embodiment of the present invention may also further have a coating on the surface for the purpose of improving corrosion resistance. The coating may be any suitable coating, for example, it may be any one of a hot-dip coating and an electroplated coating. The hot-dip coating may be, for example, a hot-dip galvanized layer, a hot-dip galvanized alloy layer (a hot-dip coating composed of an alloy of zinc, Si, Al, and other additional elements), or an alloyed hot-dip galvanized layer (alloyed coating) obtained by alloying these coatings. The hot-dip galvanized layer and the hot-dip galvanized alloy layer are preferably coatings containing less than 7% by mass of Fe, and the alloyed coating is preferably a coating containing more than 7% by mass and less than 15% by mass of Fe. In the hot-dip galvanized layer, the hot-dip galvanized alloy layer, and the alloyed coating, the components other than zinc and Fe are not particularly limited, and various compositions can be adopted within the usual range. In addition, the coating may be, for example, an aluminum coating, etc. In addition, the amount of coating adhesion is not particularly limited, and can be a general amount of adhesion.

[0206] [Mechanical properties]

[0207] According to the steel sheet of the embodiment of the present invention, a high tensile strength, specifically a tensile strength of 400 MPa or more can be achieved. The tensile strength is preferably 440 MPa or more or 480 MPa or more, more preferably 540 MPa or more or 600 MPa or more. The upper limit is not particularly limited, but for example, the tensile strength may be 980 MPa or less or 900 MPa or less. Similarly, according to the steel sheet of the embodiment of the present invention, excellent formability can be achieved, more specifically, a total elongation of 20% or more can be achieved. The total elongation is preferably 22% or more, more preferably 25% or more or 30% or more. The upper limit is not particularly limited, but for example, the total elongation may be 50% or less or 45% or less. The tensile strength and the total elongation are measured by performing a tensile test based on a JIS No. 5 test piece collected from a direction in which the length direction of the test piece becomes parallel to the rolling right-angle direction of the steel plate and in accordance with JIS Z 2241:2011.

[0208] The steel sheet of the embodiment of the present invention has high strength, specifically, a tensile strength of 400 MPa or more, but can maintain excellent appearance even after being formed by formability and press forming. Therefore, the steel sheet of the embodiment of the present invention is very useful for use as an outer plate member such as a roof, a hood, a fender, and a door, which require high design in an automobile.

[0209] <Method for manufacturing steel sheet>

[0210] Next, a preferred method for manufacturing the steel sheet according to the embodiment of the present invention will be described. The following description is intended to illustrate a characteristic method for manufacturing the steel sheet according to the embodiment of the present invention, and is not intended to limit the steel sheet to a steel sheet manufactured by the manufacturing method described below.

[0211] The method for manufacturing a steel plate according to an embodiment of the present invention is characterized in that it includes the following steps:

[0212] A hot rolling process, the hot rolling process comprising heating a slab having the chemical composition described above in relation to the steel plate to a temperature of 1100 to 1400° C. and performing finish rolling, followed by coiling at a temperature of 500 to 700° C., wherein the finish rolling ends at a temperature of 800 to 1350° C.;

[0213] A pickling step of pickling the obtained hot-rolled steel sheet;

[0214] A cold rolling process of cold rolling the pickled hot-rolled steel sheet at a reduction ratio of 20 to 90%;

[0215] The step of subjecting the obtained cold-rolled steel sheet to a primary annealing, wherein the primary annealing comprises: heating the cold-rolled steel sheet and maintaining it at a maximum heating temperature of Ac3 to 950° C. for 10 to 500 seconds, and then cooling the cold-rolled steel sheet to a cooling stop temperature of 350° C. or less by controlling the average cooling rate in the temperature range of 500 to 700° C. to 50° C. / second or more; and

[0216] The process of performing a secondary annealing on the cold-rolled steel sheet after the primary annealing, wherein the secondary annealing comprises: heating the cold-rolled steel sheet and maintaining it at a maximum heating temperature of (Ac1+20) to 820°C for 10 to 500 seconds, then controlling the average cooling rate in the temperature range of 500 to 700°C to be 30°C / second or more, and further controlling the average cooling rate in the temperature range of 200 to 500°C to be 40°C / second or more. Each process is described in detail below.

[0217] [Hot rolling process]

[0218] [Heating of slab]

[0219] First, a slab having the chemical composition described above in association with the steel plate is heated. The slab used is preferably cast in a continuous casting method from the viewpoint of productivity, but can also be manufactured by an ingot casting method or a thin slab casting method. In order to obtain a high-strength steel plate, the slab used contains a relatively large amount of alloying elements. Therefore, it is necessary to heat the slab before supplying it to hot rolling so that the alloying elements are dissolved in the slab. If the heating temperature is lower than 1100°C, sometimes the alloying elements are not fully dissolved in the slab and coarse alloy carbides remain, causing brittle cracking during hot rolling. Therefore, the heating temperature is preferably above 1100°C. The upper limit of the heating temperature is not particularly limited, but it is preferably below 1400°C from the viewpoint of the capacity of the heating equipment and productivity.

[0220] [Rough rolling]

[0221] In the present method, for example, the heated slab may be subjected to rough rolling before finish rolling in order to adjust the thickness of the slab, etc. The conditions for the rough rolling are not particularly limited as long as the desired thin slab size can be ensured.

[0222] [Finish rolling and coiling]

[0223] The heated slab or the slab that has been rough-rolled as needed is then subjected to finish rolling. Since the slab used as described above contains a relatively large amount of alloy elements, it is necessary to increase the rolling load during hot rolling. Therefore, hot rolling is preferably carried out at a high temperature. In particular, the end temperature of finish rolling is important in controlling the metal structure of the steel plate. If the end temperature of finish rolling is low, the metal structure sometimes becomes uneven and the formability decreases. Therefore, the end temperature of finish rolling is set to above 800°C. On the other hand, in order to suppress the coarsening of austenite, the end temperature of finish rolling is set to below 1350°C. Next, the hot-rolled steel sheet after finish rolling is coiled at a coiling temperature of 500 to 700°C. By setting the coiling temperature to 500 to 700°C, the growth of oxide scale can be suppressed.

[0224] [Pickling process]

[0225] Next, the obtained hot-rolled steel sheet is pickled to remove the oxide scale formed on the surface of the hot-rolled steel sheet. The pickling can be carried out under conditions suitable for removing the oxide scale, and can be carried out once or in multiple times in order to reliably remove the oxide scale.

[0226] [Cold rolling process]

[0227] The hot-rolled steel sheet after pickling is cold-rolled at a reduction rate of 20 to 90% in the cold rolling process. By setting the reduction rate of cold rolling to more than 20%, the shape of the cold-rolled steel sheet can be kept flat, and the reduction of ductility in the final product can be suppressed. On the other hand, by setting the reduction rate of cold rolling to less than 90%, it is possible to prevent the rolling load from becoming too large and rolling from becoming difficult. The number of rolling passes and the reduction rate of each pass are not particularly limited, as long as they are appropriately set in such a way that the overall reduction rate of cold rolling is within the above range.

[0228] [Primary annealing process]

[0229] The obtained cold-rolled steel sheet is heated in the next annealing process, maintained at the maximum heating temperature of Ac3 to 950°C for 10 to 500 seconds, and then cooled to a cooling stop temperature of 350°C or less by controlling the average cooling rate in the temperature range of 500 to 700°C to be 50°C / second or more. The Ac3 point (°C) is obtained by cutting a small piece from the cold-rolled steel sheet and determining the thermal expansion of the small piece during heating from room temperature to 1000°C at 10°C / second. Austenitization is promoted by maintaining the temperature above the Ac3 point for a sufficient time, and cooling to a temperature below 350°C by subsequent rapid cooling, thereby reliably forming the metal structure in the cooled steel sheet by a structure mainly composed of bainite and / or martensite, such as full bainite or full martensite. Among them, the so-called structure with bainite and / or martensite as the main body refers to a structure containing at least one of bainite and martensite of more than 90% in total area ratio, the so-called full bainite refers to a structure composed of 100% bainite in area ratio, and the so-called full martensite refers to a structure composed of 100% martensite in area ratio. Bainite and / or martensite structure is a structure having a large number of various interfaces inside compared with structures such as ferrite. Therefore, by constituting the metal structure in the steel plate before the secondary annealing process, i.e., the final annealing process, with bainite and / or martensite, it becomes possible to generate a large number of carbides that can become nucleation sites of austenite on these interfaces in a dispersed manner at the stage of heating such a metal structure in the secondary annealing. As a result, by finely and uniformly generating austenite in the entire steel plate from such a large number of dispersed nucleation sites, and then generating martensite from these austenites, in the metal structure obtained after the secondary annealing, the average grain spacing of martensite is controlled to be 2.5 μm or less, and the standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction is controlled to be 1.5% or less. That is, it is possible to achieve a metal structure in which martensite is uniformly dispersed in both the microscopic region and the macroscopic region.

[0230] In the case of not performing the first annealing process, it is of course impossible to form the metal structure in the steel plate before the final annealing (secondary annealing) process by a structure mainly composed of bainite and / or martensite. In addition, even if the first annealing process is performed, if the maximum heating temperature in the first annealing process is lower than the Ac3 point or the holding time is lower than 10 seconds, the austenitization becomes insufficient, and even by subsequent cooling, it is impossible to form the metal structure in the steel plate by a structure mainly composed of bainite and / or martensite. That is, it is impossible to set the total area ratio of bainite and martensite to more than 90%. On the other hand, heating and holding at higher temperatures and longer times will reduce productivity, so the maximum heating temperature in the first annealing process is set to below 950°C and the holding time is set to below 500 seconds.

[0231] In addition, if the average cooling rate in the temperature range of 500 to 700°C in the primary annealing process is lower than 50°C / second or the cooling stop temperature exceeds 350°C, ferrite is generated during cooling, and the total area ratio of bainite and martensite in the metal structure of the steel plate cannot be set to more than 90%. Therefore, the average cooling rate needs to be set to more than 50°C / second, and the upper limit is preferably 300°C / second. On the other hand, the lower limit of the cooling stop temperature is not particularly limited, for example, it can also be room temperature (25°C), preferably 200°C.

[0232] [Secondary annealing process (final annealing process)]

[0233] The cold-rolled steel sheet after the primary annealing is heated again in the next secondary annealing process, maintained at the maximum heating temperature of (Ac1+20)~820°C for 10 to 500 seconds, and then cooled by controlling the average cooling rate in the temperature range of 500~700°C to 30°C / second or more, and further controlling the average cooling rate in the temperature range of 200~500°C to 40°C / second or more. Among them, for the Ac1 point (°C), as in the case of the Ac3 point, a small piece is cut from the cold-rolled steel sheet, and the thermal expansion of the small piece during heating from room temperature to 1000°C at 10°C / second is obtained. First, at the stage of heating the steel sheet after the primary cooling to the maximum heating temperature of (Ac1+20)~820°C, carbides can be dispersedly generated on a large number of interfaces contained in the interior of bainite and / or martensite in the metal structure. Next, by maintaining the maximum heating temperature corresponding to the two-phase region of ferrite and austenite for 10 to 500 seconds, the state in which carbides are dispersed on the interface can be maintained, and austenite is finely and uniformly generated in the entire steel plate from the carbides. Finally, by controlling the average cooling rate in the temperature range of 500 to 700°C to more than 30°C / second, and further controlling the average cooling rate in the temperature range of 200 to 500°C to more than 40°C / second, martensite can be appropriately generated from the finely dispersed austenite, as a result, the average particle spacing of the martensite is controlled to less than 2.5μm, and the standard deviation in the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction is controlled to less than 1.5%. That is, a metal structure in which martensite is uniformly dispersed in both the microscopic region and the macroscopic region can be achieved.

[0234] If the maximum heating temperature in the secondary annealing process is lower than Ac1+20°C or the holding time is lower than 10 seconds, the desired metal structure as described above cannot be obtained, and in particular, martensite cannot be appropriately generated. On the other hand, when the maximum heating temperature exceeds 820°C, the area ratio of austenite becomes too high, and the area ratio of ferrite cannot be set to more than 80%. Furthermore, due to the high temperature, it becomes impossible to maintain the state in which carbides are dispersed on the interface, and in the final metal structure, it becomes impossible to achieve uniform dispersion of martensite in both the microscopic region and the macroscopic region. In addition, if the holding time exceeds 500 seconds, the austenite grains coarsen, and the martensite grains obtained by subsequent cooling also become relatively coarse. In such a case, it is impossible to obtain a fine martensitic structure in which the average particle spacing of martensite is controlled to be less than 2.5μm.

[0235] In addition, if the average cooling rate in the temperature range of 500 to 700°C in the secondary annealing process is lower than 30°C / second, the phase transformation from austenite to bainite, etc. will be promoted, and even if the subsequent cooling is appropriately performed, the desired amount of martensite may not be obtained. In this case, it becomes impossible to achieve the desired strength and / or it becomes impossible to achieve the uniform dispersion of martensite in the microscopic region. Therefore, the average cooling rate in the temperature range of 500 to 700°C needs to be set to 30°C / second or more, and the upper limit is, for example, 200°C / second or less, preferably 60°C / second or less. On the other hand, if the average cooling rate in the temperature range of 200 to 500°C is lower than 40°C / second, the phase transformation from austenite to martensite cannot be promoted, and the generation of other structures such as bainite increases. Therefore, the average cooling rate in the temperature range of 200 to 500°C needs to be set to 40°C / second or more, and the upper limit is, for example, 200°C / second or less, preferably 80°C / second or less.

[0236] The above method is a method for manufacturing a steel plate according to an embodiment of the present invention by performing a double annealing treatment including a primary annealing and a secondary annealing, but the steel plate according to the embodiment of the present invention is not necessarily limited to a steel plate manufactured by such a method, and can be manufactured by performing a single annealing treatment, for example. More specifically, by forming the metal structure of the steel plate after the hot rolling process with full bainite or full martensite, the single annealing described above can be omitted. However, in this case, it is necessary to appropriately control the cooling conditions and coiling temperature after hot rolling, and in addition, the control of the reduction rate in the subsequent cold rolling also becomes important. The reason is that if the reduction rate in cold rolling becomes high, recrystallization occurs during heating in the subsequent annealing process, and it becomes impossible to maintain the metal structure formed in the hot rolling process.

[0237] [Plating process]

[0238] For the purpose of improving corrosion resistance, the surface of the obtained cold-rolled steel sheet may also be subjected to plating treatment. The plating treatment may be hot-dip plating, alloyed hot-dip plating, electroplating and the like. For example, as a plating treatment, the steel sheet may be subjected to hot-dip galvanizing treatment, or alloying treatment may be performed after hot-dip galvanizing treatment. The specific conditions of the plating treatment and the alloying treatment are not particularly limited, and may be any suitable conditions known to those skilled in the art. For example, in the hot-dip galvanizing treatment, the temperature of the plating bath immersion plate (the temperature of the steel sheet when immersed in the hot-dip galvanizing bath) is preferably in the temperature range from a temperature 40°C lower than the hot-dip galvanizing bath temperature (hot-dip galvanizing bath temperature -40°C) to a temperature 50°C higher than the hot-dip galvanizing bath temperature (hot-dip galvanizing bath temperature +50°C). In the case of performing an alloying treatment on the hot-dip galvanized layer, it is preferred to heat the steel sheet formed with the hot-dip galvanized layer to a temperature range of 400 to 600°C.

[0239] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples at all.

[0240] Example

[0241] In the following examples, steel sheets according to embodiments of the present invention were produced under various conditions, and the tensile strength, formability, and appearance after forming of the obtained steel sheets were investigated.

[0242] First, molten steel is cast by continuous casting to form slabs having various chemical compositions shown in Table 1, and these slabs are heated to a specified temperature of 1100 to 1400°C and hot rolled. Hot rolling is carried out by performing rough rolling and finish rolling, and the end temperature and coiling temperature of the finish rolling are as shown in Table 2. Next, the obtained hot-rolled steel sheet is pickled, and then cold rolled at the reduction rate shown in Table 2 to obtain a cold-rolled steel sheet having a sheet thickness of 0.4 mm. Next, the obtained cold-rolled steel sheet is subjected to primary annealing and secondary annealing under the conditions shown in Table 2. Finally, as a plating treatment, hot-dip galvanizing is preferably performed, and then several of the steel sheets are alloyed at the alloying temperature shown in Table 2.

[0243]

[0244]

[0245]

[0246] The properties of the obtained steel sheets were measured and evaluated by the following methods.

[0247] [Tensile strength (TS) and total elongation (El)]

[0248] The tensile strength (TS) and the total elongation (El) were measured by performing a tensile test in accordance with JIS Z2241:2011 based on a JIS No. 5 test piece collected in a direction parallel to the rolling direction of the steel sheet in the longitudinal direction of the test piece.

[0249] [Appearance after molding]

[0250] The appearance after forming is evaluated by the degree of ghost lines produced on the surface of the door outer panel component that has been given a strain of about 5% due to press forming. The surface after press forming is polished with a grinder, and the straight stripe pattern produced on the surface and extending roughly parallel to the rolling direction is judged as a ghost line for evaluation. An arbitrary area of ​​100mm×100mm is visually confirmed, and the case where no stripe pattern is confirmed at all is judged as qualified (0), and the case where a stripe pattern is confirmed is judged as unqualified (×). In this test, the appearance after forming is actually evaluated by press forming the door outer panel component, but it is also possible to use a formed component that can be presumed to have been given a strain of about 5% due to press forming as an evaluation object, and it is also possible to use a test piece collected from a steel plate that has been given a pre-strain of 5% as an evaluation object. The same results can be obtained by such a test method. In the case of a test piece collected from a steel plate, the evaluation can be performed on a test piece to which a 5% prestrain is applied with respect to a JIS No. 5 test piece having a longitudinal direction perpendicular to the rolling direction and the plate thickness direction.

[0251] Steel sheets having a tensile strength (TS) of 400 MPa or more, a total elongation (El) of 20% or more, and a pass in the appearance evaluation after forming were evaluated as steel sheets that can achieve both strength and formability and appearance after forming.

[0252]

[0253] Referring to Tables 1 to 3, Comparative Example 16 has a high C content, so TS becomes too high and El decreases. Comparative Example 17 has a high Mn content, so ferrite transformation is suppressed, and El decreases in the same manner. It is believed that Comparative Example 18 has insufficient austenitization due to the low maximum heating temperature of the first annealing process, and even through subsequent cooling, the metal structure in the steel plate cannot be formed by a structure with bainite and / or martensite as the main body. As a result, the average particle spacing of martensite in the metal structure obtained after the second annealing becomes more than 2.5μm, and the standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction becomes more than 1.5%, and the appearance after forming is reduced. It is believed that Comparative Example 19 cannot fully undergo a transformation from austenite to bainite and / or martensite due to the high cooling stop temperature of the first annealing process. As a result, the average particle spacing of martensite in the metal structure obtained after the second annealing becomes more than 2.5μm, and the standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction becomes more than 1.5%, and the appearance after forming is reduced. It is believed that Comparative Example 20 is not able to fully perform the phase transformation from austenite to bainite and / or martensite because the average cooling rate in the temperature range of 500-700°C in the first annealing process is slow. As a result, the average particle spacing of martensite in the metal structure obtained after the second annealing becomes more than 2.5μm, and the standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction exceeds 1.5%, and the appearance after forming is reduced. Comparative Example 21 has a high maximum heating temperature in the second annealing process, so austenitization is excessively carried out, and the desired amount of ferrite is not obtained in the metal structure after cooling. In addition, a large amount of residual structure is also generated, and uniform dispersion of martensite in both microscopic and macroscopic regions cannot be achieved. As a result, both the formability and the appearance after forming are reduced. It is believed that the austenite grains of Comparative Example 22 are coarsened due to the long holding time in the secondary annealing process. As a result, the average particle spacing of martensite in the metal structure obtained after the secondary annealing exceeds 2.5μm, and the appearance after forming is reduced. Comparative Example 23 promotes the phase transformation from austenite to bainite, etc. due to the low average cooling rate in the temperature range of 500-700°C in the secondary annealing process, and the desired amount of martensite is not obtained. As a result, the average particle spacing of martensite in the metal structure obtained after the secondary annealing exceeds 2.5μm, and the appearance after forming is reduced. Comparative Example 24 cannot promote the phase transformation from austenite to martensite due to the low average cooling rate in the temperature range of 200-500°C in the secondary annealing process, and a large amount of bainite is generated in the same manner. As a result, the average particle spacing of martensite in the metal structure obtained after the secondary annealing similarly exceeds 2.5μm, and the appearance after forming is reduced.For Comparative Examples 22 to 24, although the standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction is less than 1.5%, the average particle spacing of martensite exceeds 2.5μm, that is, although the uniformity of martensite in the macroscopic region is ensured, the uniformity of martensite in the microscopic region is not ensured. Therefore, for these comparative examples, it is believed that the appearance after forming is reduced due to the presence of uneven martensite locally. Since Comparative Example 25 does not perform the first annealing process, it is impossible to form the metal structure in the steel plate before the second annealing process by a structure with bainite and / or martensite as the main body. As a result, the average particle spacing of martensite in the metal structure obtained after the second annealing becomes more than 2.5μm, and the standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction becomes more than 1.5%, and the appearance after forming is reduced. In Comparative Example 26, since the maximum heating temperature in the secondary annealing step was low, martensite could not be appropriately generated in the metal structure after cooling, and the desired TS could not be obtained.

[0254] In contrast, in all the inventive examples, by having a predetermined chemical composition and appropriately controlling the ratio of ferrite and martensite in the metal structure, a TS of 400 MPa or more and an El of 20% or more can be achieved, and by controlling the average particle spacing of martensite to 2.5 μm or less in the microscopic region and controlling the standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the plate thickness direction to 1.5% or less in the macroscopic region, even when strain is imparted by press forming, the generation of microscopic concavities and convexities on the surface of the steel sheet can be suppressed and the generation of ghost lines can be significantly suppressed. The metal structure of the cold-rolled steel sheets before the secondary annealing of all the inventive examples was observed in cross section, and the results showed that they were composed of martensite with an area ratio of 90% or more.

Claims

1. A steel plate, characterized in that: It has the following chemical composition in mass %: C: 0.03-0.08%, Si: 0.01-1.00%, Mn: 0.50~3.00%, P: 0.1000% or less, S: 0.0200% or less, Al: 1.000% or less, N: 0.0200% or less, O:0~0.020%、 Cr:0~2.000%、 Mo: 0~1.000%, Ti: 0~0.500%, Nb: 0~0.500%, B:0~0.0100%、 Cu: 0~1.000%, Ni: 0-1.00%, W:0~0.100%、 V:0~1.000%、 Ta: 0~0.100%、 Co: 0~3.000%, Sn: 0~1.000%, Sb: 0~0.500%, As: 0~0.050%, Mg: 0~0.050%, Zr:0~0.050%、 Ca: 0~0.0500%, Y:0~0.0500%、 La: 0~0.0500%, Ce: 0~0.0500%, Bi: 0 to 0.0500%, and The rest: consists of Fe and impurities; The steel plate has the following metal structure: The area ratio is composed of the following: Ferrite: 80-95%, Martensite: 5-20%, and At least one of bainite, pearlite and retained austenite: 0 to 10% in total, and the average grain spacing of martensite is 2.5 μm or less, The standard deviation of the area ratio of martensite in the direction perpendicular to the rolling direction and the sheet thickness direction is 1.5% or less.

2. The steel plate according to claim 1, characterized in that: The chemical composition includes at least one of the following elements in mass %: Cr:0.001~2.000%、 Mo: 0.001~1.000%, Ti: 0.001~0.500%, Nb: 0.001~0.500%, B:0.0001~0.0100%、 Cu: 0.001~1.000%, Ni: 0.001~1.00%, W:0.001~0.100%、 V:0.001~1.000%、 Ta: 0.001~0.100%, Co: 0.001~3.000%, Sn: 0.001~1.000%, Sb: 0.001~0.500%, As: 0.001~0.050%, Mg: 0.0001~0.050%, Zr:0.0001~0.050%、 Ca: 0.0001 to 0.0500%, Y: 0.0001 to 0.0500%, La: 0.0001 to 0.0500%, Ce: 0.0001 to 0.0500%, and Bi: 0.0001 to 0.0500%.

Citation Information

Patent Citations

  • Steel sheet for hot dip galvanizing and hot dip galvannealed steel sheet

    JP2009249737A

  • Cold-rolled steel sheet and method for producing same

    WO2011142473A1